Introduction to statistical pattern recognition - Fukunaga, Keinosuke (Boston : Academic Press, 1990)
This revised second edition presents an introduction to statistical pattern recognition. Pattern recognition in general covers a range of problems: it is applied to engineering problems, such as character readers and wave form analysis as well as to brain modeling in biology and psychology.
Cover; Frontmatter; Chapter 1: Introduction; Chapter 2: Random Vectors and Their Properties; Chapter 3: Hypothesis Testing; Chapter 4: Parametric Classifiers; Chapter 5: Parameter Estimation; Chapter 6: Nonparametric Density Estimation; Chapter 7: Nonparametric Classification and Error Estimation; Chapter 8: Successive Parameter Estimation; Chapter 9: Feature Extraction and Linear Mapping for Signal Representation; Chapter 10: Feature Extraction and Linear Mapping for Classification; Chapter 11: Clustering; Backmatter; Back Cover
Includes bibliographical references and index.
Keywords: Pattern perception -- Statistical methods; Decision making -- Mathematical models; Mathematical statistics; Electronic books